TANGGUNG JAWAB DEBITUR TERHADAP MUSNAHNYA BENDA JAMINAN FIDUSIA DALAM PERJANJIAN KREDIT BANK - AMALIA YULIA NASTITI (PREMISE LAW JURNAL, 2016)
In its implementation, credit contract with fiduciary collateral, certificate of fiduciary collateral made by a Notary and registered electronically by the Notary. A creditor only holds it and other documents which are related to the collateral as security when there is something occurs in its implementation. The research used judicial normative and descriptive analytic method. The result of the research showed that the binding of fiduciary collateral in a banking credit contract is preceded by a feasibility study, administration and collateral, fiduciary certificate made by Notary, and its registration electronically, and the signing of insurance polis. A debtor who gives fiduciary collateral has to be liable for the Bank as the creditor upon the disappearance of fiduciary collateral. Keywords: Debtor’s Liability, Fiduciary Collateral, Banking Credit Contract